EVALUATION OF MORPHOGENESIS AND REGENERATION OF HARD SPRING WHEAT IN VITRO - Bychkova, O. V. (Acta Biologica Sibirica, 2016)
We estimated the morphogenetic and regenerative capacity of six varieties of hzrd spring wheat of different ecological and geographical origin in the culture of immature embryos in vitro. The efficiency of re-differentiation of cell line genotypes under the stress and in control. The morphogenesis rate was higher in 2015 (91.5%), in conditions of stress (2014) it was 87.2%. We revealed mixed reaction of studied genotypes of summer durum wheat on regeneration rate. We determined the input of principal factors influencing the variability of calusogenesis, morphogenesis, and regeneration.